Consequences of Moral Outrage among Nurses: A Scoping Review - Sima Pourteimour; Abbasali Ebrahimian; Hesamedin Askari-Majdabadi; Naser Parizad; Ali Fakhr-Movahedi (Iranian Journal of Nursing and Midwifery Research)
Background: Clinical nurses often encounter situations that challenge their professional integrity and values. In the face of these issues, many nurses have been subjected to moral outrage (MO) in response to moral violations by others, which can have different outcomes. This scoping review aimed to synthesize and summarize findings from existing articles regarding the consequences of moral outrage among nurses. Materials and Methods: This paper presents a scoping review based on the Joanna Briggs Institute (JBI) methodology. PubMed, Springer, Scopus, and ScienceDirect databases were systematically searched using the keywords “moral outrage”, “nurses or nursing” and “consequences or outcomes or impacts or effects or influences of moral outrage” (viz., moral OR ethical AND outrage AND nurse*). The PRISMA checklist was used for the scoping review to evaluate articles thoroughly. The results were summarized using the inductive content analysis suggested by Elo and Kyngäs. Results: In total, 1014 articles were identified as potentially relevant to this study with 34 articles synthesized, including 24 qualitative studies, 5 quantitative studies, and 5 reviews focused on the consequences of moral offenses in nursing. Negative consequences such as mental exhaustion, job burnout, and interpersonal failures were observed, alongside positive consequences like nurses’ altruism, callousness, and professional solidarity. Conclusions: These findings underscore the importance of addressing MO among nurses to prevent negative consequences such as burnout and moral degradation. Moreover, recognizing and fostering the altruistic and resilient aspects of nurses in response to moral outrage can lead to a more positive work environment and improved patient care.